Pricing Standardized Mortality Securitizations: A Two‐Population Model With Transitory Jump Effects. Issue 3 (29th August 2013) - Zhou, Rui; Li, Johnny Siu‐Hang; Tan, Ken Seng
Abstract : Mortality dynamics are subject to jumps that are due to events such as wars and pandemics. Such jumps can have a significant impact on prices of securities that are designed for hedging catastrophic mortality risk, and therefore should be taken into account in modeling. Although several single‐population mortality models with jump effects have been developed, they are not adequate for modeling trades in which the hedger's population is different from the population associated with the security being traded. In this article, we first develop a two‐population mortality model with transitory jump effects, and then we use the proposed model and an economic‐pricing framework to examine how mortality jumps may affect the supply and demand of mortality‐linked securities.